RESPIRATORY MUSCLE TRAINING METHODS FOR IMPROVING THE LUNG CAPACITY OF PROFESSIONAL VOCALISTS AND WIND INSTRUMENTISTS - Rareș NICOARĂ; Dan MONEA (Cluj University Press, 2021)
Introduction: Various muscle groups are involved in pulmonary ventilation, which play an essential role in maintaining proper breathing, their development being aimed at improving the physical, psychological and qualitative performance of the performance of professional singers and blowers in instruments. Objectives: The objectives of the training of the respiratory muscles are aimed at improving dyspnea, toning the respiratory muscles, increasing the efficiency of the respiratory muscles, increasing the volumes of air mobilized, decreasing the fan labor, controlling and coordinating the respiratory rhythm. Methods: The study subjects were 9 young musicians, students at the Conservatory in the singing and wind instruments sections, who performed workouts with a threshold device (POWERBreathe Inspirational Muscle Training IMT), five days a week, twice a day, for 6 weeks. Subjects performed spirometry tests VC, FVC, FEV1, FEV1/FVC, VF, FEV6 at each beginning and end of the meeting, the data collected were processed by interpreting the results of lung function and flow measurements. Results: The results obtained from the spirometry tests show us statistically significant differences between the initial (IT) and the final (IT) test. Thus, at the first sit, with the device adjusted to max.15% PI/PE (inspiratory - expiratory pressure), the average of the VC values, FVC, FEV1, VF, FEV6 (5.72 - 5.84l, l/s) increased by 2%, and at the end of the second session, with the device set to min.40-60% PI/PE, the average lung function values (5.72 - 6.14l, l/s) increased by 9.8%. Conclusions: This experiment can demonstrate that the acute effect of training with a breathing device (threshold) results in a significant increase in the use of flow during singing and blowing, leading to a sound with a higher acute sound and more activity. REZUMAT. Metode de antrenament a musculaturii respiratorii pentru îmbunătățirea capacității pulmonare a profesioniștilor vocali și suflătorilor instrumentiști. Introducere: În ventilația pulmonară sunt implicate diverse grupe musculare care au rol esențial în menținerea unei respirații corespunzătoare, dezvoltarea lor fiind menită să îmbunătățească performanțele fizice, psihologice și calitative ale prestației cântăreților profesioniști și suflătorilor în instrumente. Obiective: Obiectivele antrenamentului mușchilor respiratori au ca scop ameliorarea dispneei, tonifierea musculaturii respiratorii, creșterea eficienței mușchilor respiratori, creșterea volumelor de aer mobilizate, scăderea travaliului ventilator, controlarea și coordonarea ritmului respirator. Metode: Subiecții studiului au fost 9 tineri muzicieni, studenți la Conservator la secțiile de canto și instrumente de suflat, care au efectuat antrenamente cu un dispozitiv threshold (POWERBreathe Inspiratory Muscle Training IMT), cinci zile pe săptămână, de două ori pe zi, timp de 6 săptămâni. Subiecții au efectuat teste spirometrice VC, FVC, FEV1, FEV1/FVC, PEF, FEV6 la fiecare început și sfârșit de ședință, datele colectate au fost prelucrate prin interpretarea rezultatelor funcției pulmonare și a măsurătorilor de debit. Rezultate: Rezultatele obținute la testele spirometrice ne arată diferențe semnificative statistic între testarea inițială (TI) și cea finală (TI). Astfel, la prima ședință, cu dispozitivul reglat la max. 15% PI/PE (presiune inspiratorie - expiratorie), media valorilor VC, FVC, FEV1, PEF, FEV6 (5.72 - 5.84l, l/s) a crescut cu 2%, iar la sfârșitul celei de-a doua ședințe, cu dispozitivul setat la min.40-60% PI/PE, media valorilor funcției pulmonare (5.72 - 6.14l, l/s) a crescut cu 9.8%. Concluzii: Acest experiment poate demonstra că efectul acut al antrenamentului cu un dispozitiv de prag respirator (threshold) are drept consecință o creștere semnificativă a utilizării debitului în timpul cântului, ceea ce duce la un sunet cu o sonoritate acută mai mare și cu mai multă activitate. Cuvinte cheie: mușchi respiratori, antrenament, capacitate de efort.